2009
DOI: 10.1021/jp809386c
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Hydrated Electrons with Guanine Derivatives: Tautomerism of Intermediate Species

Abstract: Here, we show that two tautomers are produced by the protonation of the guanine-electron adduct. The fate of electron adducts of a variety of substituted guanosines was investigated by radiolytic methods and addressed computationally by means of time-dependent DFT (TD-B3LYP/6-311G**//B1B95/6-31+G**) calculations. The reaction of e(aq-) with guanosine and 1-methylguanosine produces two transient species, whereas the reaction with N2-ethylguanosine and N2,N2-diethylguanosine produces only one. The two short-live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…The latter species may undergo further reactions with H 2 O or radicals in the reaction mixture. 32 Figure 5 shows our proposed mechanism of d(GpTpG) release from a GTG-cisPt complex following reaction with a single e − aq , by a two-step process. Adam et al have shown using transient absorption measurements at 310 nm that Pt II can be reduced by e − aq and also by H • radicals (k = 1.2 × 10 10 mol −1 L s −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The latter species may undergo further reactions with H 2 O or radicals in the reaction mixture. 32 Figure 5 shows our proposed mechanism of d(GpTpG) release from a GTG-cisPt complex following reaction with a single e − aq , by a two-step process. Adam et al have shown using transient absorption measurements at 310 nm that Pt II can be reduced by e − aq and also by H • radicals (k = 1.2 × 10 10 mol −1 L s −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rate constants of 6 Â 10 9 and 7.9 Â 10 9 M À1 s À1 were obtained for the reaction of HO • radical with N 2 -ethyl-2 0 -deoxyguanosine (21) and N 2 ,N 2 -diethyl-2 0 -deoxyguanosine (24), respectively (Scheme 8). Figure 6 shows the spectral changes obtained from the pulsed irradiation of N 2 O saturated aqueous solution (unbuffered) of 1 mM 21.…”
Section: Chemical Research In Toxicologymentioning
confidence: 99%
“…This pathway could explain the absence of further consumption of 8-TG in the predominant presence of HO • radicals. Additionally, the intermediate E could be directly formed by Br 2 •− and N 3 • and provide regeneration of 1 in the same fashion, explaining the comparable results in the presence of these two radical species [31,51,52].…”
Section: Resultsmentioning
confidence: 83%
“…In fact, in all the reactions we could observe similar results to the ones obtained in the previous experiments in terms of G values, while no further consumption of the substrate was achieved via side product formation. On the basis of our strong background of radical chemistry of guanosine derivatives [31,47,48,49,50,51,52], it was established that HO • radicals could perform hydrogen abstraction predominantly on the exocyclic NH 2 group [48,49,50], leading to the radical intermediate D (Scheme 5). This species could undergo tautomerization to the more stable radical E .…”
Section: Resultsmentioning
confidence: 99%